2014
DOI: 10.3109/14767058.2014.957668
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on anticipated quality-of-life and recommendations for neonatal intensive care: a survey of neonatal providers

Abstract: The perspectives of practitioners who provide care to critically ill neonates regarding potential survival and QOL vary dramatically and are associated with the treatments those practitioners recommend. Practitioners should take care to avoid basing treatment recommendations on their own perspectives if they are not well aligned with those of the parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Finally, attitudes toward quality of life constitute an important value‐laden, but very real, practical concern. Data suggest that expectations of quality of life from physicians are associated with their recommendation about life‐sustaining intervention . Studies have shown that physicians underestimate the outcomes for neonates .…”
Section: The ‘Our‐hope’ Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, attitudes toward quality of life constitute an important value‐laden, but very real, practical concern. Data suggest that expectations of quality of life from physicians are associated with their recommendation about life‐sustaining intervention . Studies have shown that physicians underestimate the outcomes for neonates .…”
Section: The ‘Our‐hope’ Approachmentioning
confidence: 99%
“…There is an impressive body of research reporting differences in parent, child, and clinician ratings about quality of life, often showing a more pessimistic outlook by clinicians (e.g. the disability paradox) . However, the ratings of quality of life by parents are not always higher than physicians .…”
Section: The ‘Our‐hope’ Approachmentioning
confidence: 99%
See 3 more Smart Citations